If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-1)=2x-3+3
We simplify the equation to the form, which is simple to understand
3(x-1)=2x-3+3
Reorder the terms in parentheses
+(+3x-3)=2x-3+3
Remove unnecessary parentheses
+3x-3=+2x-3+3
We move all terms containing x to the left and all other terms to the right.
+3x-2x=-3+3+3
We simplify left and right side of the equation.
+1x=+3
We divide both sides of the equation by 1 to get x.
x=3
| 8w=9+9w | | 6x^2-10x-7=0 | | (x/4)+8=-8 | | X=10x-12 | | Y^2-y+.25=0 | | 5=8m+4-7 | | 37-2x=6+7(-3x-1) | | -5+5m=-10+4m | | -4+q=-13 | | 64x^2-5=30 | | -3p=-2p-9 | | 10(c-2)+5=3+c-18 | | 124-9w=3 | | 5x-4=2(x-2)+3x | | 12y-5y=15 | | x^2-1.5x+.5625=0 | | 1.3x+2.3=0.6x-4.07 | | -9c=8-10c | | 9a+2b+8a-3b= | | 2a+6y=2 | | 3+p=15 | | -3n=-4n+7 | | 6x-3=15x-15 | | 18x^2+73x-36=0 | | 36x^2-5=95 | | 2x+1=-31 | | 1-x-x=-9 | | x-5+3=-2 | | -2u-7=-3u | | 3.14r^2=225(3.14) | | 8x^2+6x-65=0 | | [h]-4=9 |